The Least Developed Countries Report 2018 - United Nations Conference on Trade; Development (United Nations, 2018)
For Least Developed Countries (LDCs) to progress towards the Sustainable Development Goals, they need to transform the structure of their economy. This, in turn, requires entrepreneurship that innovates. The entrepreneurial landscape in LDCs is dominated by micro and small enterprises with low chances of survival and growth, and scant innovation. While LDCs are part of global value chains, these provide only limited opportunities of entrepreneurship development and upgrading. Most LDCs policies and programmes for entrepreneurship aim at job creation, poverty reduction and women and youth empowerment. For entrepreneurship to be a driving force towards structural transformation, policies need to target and support high-potential firms.